Osteoblast Number in Tension Area by Giving Propolis Extract As Orthodontic Relaps Prevention - Budi Handayani; Arya Brahmanta (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2018)
Background: relapse is often happen after orthodontic treatment finished. Propolis contains flavonoid, saponin and CAPE that known increase the number of osteoblast. Osteoblast have important role in bone remodeling which can prevent relapse. Purpose: to determine increasing number of osteoblast in bone remodeling after the giving 3% and 5% of propolis to prevent relapse after orthodontic treatment. Materials and metode: the design of this study was randomized post testonly control group design. 28 guine pig were divided into 4 groups of K- (without treatment), K+ ( giving separator rubber), P1( giving separator rubber and 3% propolis), P2 ( giving separator rubber and 5% propolis). Result: There are increasing number of osteoblast in the tension side of alveolar bone in treatment group. The average number of osteoblast in the tension side of alveolar bone in group K-:26.86; K+:33,29; P1:41.29; P2:48.29. Conclusion: giving 5% of propolis is the most effective I increasing the number of osteoblast in tension side of alveolar bone in relapse after orthodontic treatment.